Mineral Prospect in Simpang Tiga, Aceh Besar - Siti Makfiroh; Suhrawardi Ilyas; Muhammad Sukri (PSI-Aceh, 2012)
Simpang Tiga is one district in Aceh Besar that currently supply rock and building materials for construction in Banda Aceh. Geologically, Simpang Tiga is formed by sedimentary rocks and carbonate minerals. This study aims is to identify the types of minerals in Simpang Tiga that has economic value. In this study the samples are identified using naked eye and optical microscope to identify more clearly. After that, the comparison with catalogue is made. HCl is used to identify carbonate type minerals. The results indicate that there are classes of carbonate mineral that are calcite (CaCO3) and dolomite (CaMg (CO3)2). Oxide groups with the type of mineral are the mineral magnetite (Fe3O4), hematite (Fe2O3), magnesium (MgO) and agate (SiO2). Group with the type of mineral silica is a mineral biotite (K(Mg,Fe)3 (AlSi3)O10(OH, F)2. Result shows that Simpang Tiga have deposit of carbonate and oxide type of mineral, which are potential for economic development, building materials and industrial materials such as cement raw material and iron ore.